NOT SO INNOCENT INDAPAMIDE - Aziz, Shayan; Abdullah; Satyan Rajbhandari (Journal of Ayub Medical College Abbottabad, 2023)
A 58-year-old asymptomatic man was referred by his general practitioner for abnormal blood results. Routine blood tests to monitor blood count and kidney functions showed neutropenia and hyponatremia. He was euvolemic on examination. Further detailed investigation did not reveal any cause of neutropenia and hyponatremia. After careful assessment of drug history, it transpired he recently started Indapamide for uncontrolled hypertension. Hyponatraemia is a common side effect of Indapamide and in addition, it can rarely cause agranulocytosis and leukopenia. Indapamide was stopped and the blood counts started to improve and became normal after two weeks.